“Besides Moreover However and but” Conjunctions—Order Out of Confusion - Jordan, Michael P. (Journal of Technical Writing and Communication, 1974)
Few technical writers and editors understand the roles and importance of conjunctions. In fact, many find it hard to distinguish between otherwise and alternatively, between while and whereas, and between however and hence—imprecisions that too often lead to unclear writing or even technical inaccuracies. This paper uses a practical linguistic approach to describe word types that couple sentence patterns: those that subordinate a clause to the main part of a sentence pattern; those that conjoin clauses, phrases, or words; and those that connect clauses together. A “Table of Couplers” groups the main conjunctions into sub-sets according to meaning, thus allowing comparison and easy selection of the most appropriate word.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC83dDE2LXRnZTYta2RqZy0xcDJl